Mana Maori: questions of authority on the East Coast during the nineteenth century - Smit, Grace (Thesis MA–History–University of Auckland., 1997)
Keywords: leadership; new zealand wars; ngāti kahungunu; ngāti rākaipaaka; print only; rangatiratanga; wairoa

He Koha Kei Roto: He Utu Kei Waho - Kohere, Rarawa D. (ResearchSpace@Auckland, 1992)
This research focuses on the period 1830 to 1992 and is a descriptive account as well as an analysis of Ngati Piritai interaction with Pakeha over that time. This thesis details a history of struggle for control over the legitimacy and validity of the Ngati Piritai cultural imperative within a social context characterised by dominant Pakeha and subordinate Maori relations. It draws upon a range of sources and brings together the experiences of an historical sampling of Ngati Piritai whanau members covering a six generation framework of Maori - Pakeha interactions. An examination of Pakeha efforts to establish hegemonies of colonisation over Maori through educational indices is made using the critical frameworks of educational theorists such as Giroux, Bernstein, Bourdieu, Gibson, Apple, Marcuse, Shuker, and Dale. Conversely Maori efforts to maintain their cultural identity and their culture, 'per se', through counter hegemonic processes such as the control over educational frameworks are also examined. For example the control over knowledge and how such control relates to enhancing social mobility, attaining outcomes of social justice, and delivering more equitable educational outcomes are also explored. A major argument is that Maori - Pakeha inter-relations can be more clearly understood through a critical appreciation of the fundamental opposition; a Pakeha imperative for cultural dominance: assimilation on the one hand, and a Maori imperative for cultural recognition: survival, on the other. Of significance are the ways in which the dialectic between these fundamental oppositions are mediated and transformed by Ngati Piritai as they live out their lives in a societal context of contested power relations.
Keywords: print only

'Te Wai-Kaukau o nga matua tipuna': myths, realities, and the determination of mana whenua in the Waikaremoana district. - Wiri, Robert K. J. (ResearchSpace@Auckland, 1994)
In the heart of the North Island of New Zealand lies a mountainous terrain called Te Urewera, the spiritual homeland of the Tϋhoe people. Hidden away in the southern portion of Te Urewera is Waikaremoana, a lake and a land with a history and tradition that are as fascinating as they are controversial. Waikaremoana is the 'tūrangawaewae' of the Ngāti Ruapani section of Tūhoe, and it is they and their lands that are the key focus of this M.A thesis. This thesis deals essentially with the concept of land ownership or mana whenua. It analyses the relationship between customary and colonial concepts of mana whenua in the Waikaremoana district, and examines the conflicting nature of these two different cultural concepts of the land and its history. In many ways this dissertation is unique, as it is a tribal history written by tangata whenua for tangata whenua. It allows today's tangata whenua to see their history through their predecessor's eyes and reawakens the past struggles of their ancestors. It gives tangata whenua a sense of dignity and pride in their heritage and traditions that give them their identity. 'Ko te uri o Tūhoe, moumou kai, moumou tāonga, moumou tangata ki te pō!'
Keywords: iwi; mana whenua; tino rangatiratanga

Maori Affairs policies 1984-1994 and Maori Trust Boards - Sullivan, Ann (Thesis D. Phil. Political Science–University of Waikato., 1995)
Keywords: crown policy; government; government relations; history; kāwanatanga

Maori land development schemes, 1945-1974, with two case studies from the Hokianga - Harris, Aroha (Massey University, 1996)
This thesis is a study of Maori land development schemes during the period 1945 to 1974, and contains two case studies from the Hokianga. Apirana Ngata introduced the schemes to New Zealand's legislature in 1929, giving the state direct legal and financial responsibility for assisting Maori people to develop and farm Maori land. The thesis briefly outlines the historical background to the schemes, and their social objectives. It details the development scheme legislation and policy, including its practical implementation and administrative structure. The two case studies reveal the complexities of the schemes at a local operational level, and shifts in the department's policies and approach since the 1930s. Title improvement policies have been integral to the operation of the schemes. The government has consistently viewed multiple ownership of Maori land as an impediment to bringing Maori land into full production, and the schemes relied on various devices for improving Maori land title to facilitate secure tenure arrangements for Maori farmers (including sole ownership) and to allow land development to occur. These various devices include consolidation, conversion and amalgamation. Ultimately though, the prolonged emphasis on title improvement was unwarranted. The legislation made ample provision for development to occur regardless of the number of owners or the state of the title. During their first twenty years, the schemes provided subsistence level farming. They, supported many Maori communities through depression and war, provided modern conveniences in modern homes, and reasonable incomes for families. Maori farmers and land owners responded variously to the schemes. Some were completely comfortable with the schemes, others struggled. But ultimately, the large-scale corporately run schemes would have the best chance of surviving as long term propositions. The smaller farms would eventually bow to the pressure of the demands of changing overseas markets. In the post-war years, the Department of Maori Affairs increasingly bureaucratised and formalised its land development programme, and pressed ahead with reforming Maori land titles. In the process, the department became responsible for ensuring the long term success of the schemes, and protecting the interests of the parties involved, including itself, the public, and the owners and occupiers of the schemes. The overall effect of the department's policies was to create a protected environment in which the department assisted Maori farmers into the modern farming industry, while protecting them from the cruelty of the modern economy. This thesis looks at how these things occurred by reconstructing the policy and legislation that created and maintained the schemes, discussing some of the key issues and difficulties that arose, and drawing on the experiences of the two schemes that are the subjects of the case studies in chapter five. A great shift in policy occurred as government struggled to balance its socio-economic responsibilities to Maori people and its economic responsibilities to the nation. Ultimately, schemes that began as a response to local development needs in Maori communities, emerged in the 1970s as primarily concerned with maximising the production potential of Maori land, for the benefit of the national economy.
Keywords: crown policy; land development